2022
DOI: 10.1186/s42836-021-00109-0
|View full text |Cite
|
Sign up to set email alerts
|

What’s new in artificially intelligent joint surgery in China? The minutes of the 2021 IEEE ICRA and literature review

Abstract: Objective To outline the main results of the 2021 International Conference on Robotics and Automation (ICRA 2021) of the Institute of Electrical and Electronics Engineers (IEEE) and review the advances in artificially intelligent joint surgery in China. Methods The keynote speeches of the 2021 ICRA were summarized in detail, and publications indexed by five core electronic databases (PubMed, Cochrane, Medline, Embase and CNKI) were systematically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…To achieve adequate coverage (minimally 70% of the acetabular cup surface 13 ), previous studies have recommended autologous bone grafting, trabecular metal augmentation, and 3D‐printed integral customized acetabular component (oblong cup) for reconstruction, or compromising techniques such as the medial protrusion (cotyloplasty), high inclination angle, elevated hip center, and the use of extra‐small cups at the true acetabulum 4 . However, it remains disputable whether these techniques are beneficial for reconstructing the acetabulum in DDH patients because of various complications and uncertain clinical outcome, which were reported as the absorption and collapse of structural bone grafting, infection predisposition, deficiency in fitting‐in with the host bone stock, and cost‐effectiveness disadvantage of metal augmentation and 3D‐printed integral customized cup 2,14 . In this study, we identified the extra‐articular blocking as a novel but reliable technique in acetabular reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve adequate coverage (minimally 70% of the acetabular cup surface 13 ), previous studies have recommended autologous bone grafting, trabecular metal augmentation, and 3D‐printed integral customized acetabular component (oblong cup) for reconstruction, or compromising techniques such as the medial protrusion (cotyloplasty), high inclination angle, elevated hip center, and the use of extra‐small cups at the true acetabulum 4 . However, it remains disputable whether these techniques are beneficial for reconstructing the acetabulum in DDH patients because of various complications and uncertain clinical outcome, which were reported as the absorption and collapse of structural bone grafting, infection predisposition, deficiency in fitting‐in with the host bone stock, and cost‐effectiveness disadvantage of metal augmentation and 3D‐printed integral customized cup 2,14 . In this study, we identified the extra‐articular blocking as a novel but reliable technique in acetabular reconstruction.…”
Section: Discussionmentioning
confidence: 99%